DIVERSITY OF MACROZOOBENTHOS IN KUALA INDRAGIRI COASTAL WATER RIAU PROVINCE - Habonaran, Jonathan; Nasution, Syafruddin; ', Thamrin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was conducted in February 2015 located in the coastal area of Kuala Indragiri, Riau Province. This purpose of this study was to know the diversity macrozoobenthos and observe the relevance sediment content organic matter with the abundance of macrozoobenthos. The method used in the study was a survey method. Sampling macrozoobenthos was conducted by using 50 meters transect line, from the lowest tide limit to the highest tides and on each transect three plots with a size of 1 x 1 m2 was applied. The research recorded 13 spesies of macrozoobenthos consisting of 4 classes, namely class Gastropoda (Telescopium Telescopium, Eupleura caudata Chicoreus capucinus, Strombus sp, sp Cherithidea, Nerita sp, Babylonia spirata, Morulla striata), Bivalves (Anadara granosa, Placuna placenta), Crustaceans (Uca coartata, Sylla serrata), and Polychaetes (Eunice viridis). Diversity of macrozoobenthos was medium, nothing species dominates and uniformity was evenly. The average content of organic matter was 7.23%. Correlation of sediment organic matter with abundance macrozoobenthos was significant r = 0.907.Keywords: Diversity, Macrozoobenthos, Sediment Content Organic Matter, Indragiri Hilir.